Hospital Quality Service and Patient Satisfaction : How The Role of Service Excellent and Service Quality ? - Dewiana Novitasari (Journal of Information Systems and Management (JISMA), 2022)
The purpose of this study was to analyze Relationship between Service Excellent and Quality Service , Relationship between Service Excellent and Patient Satisfaction, Relationship between Service Quality and Quality Service , Relationship between Service Quality and Patient Satisfaction. The data is obtained through questionnaires distributed online through social media, the respondents of this study were 400 employees of the hospitals in Banten who were selected through simple random sampling method. Analysis of data processing using Structural Equation Modeling (SEM) with SmartPLS 4.0 software tools. The stages of PLS ​​analysis using smartpls 3 include 3 stages, namely: The outer model testing phase to test the validity & reliability of indicators and constructs, the Goodness of fit model testing phase to test the model's predictive power and model feasibility, The inner model testing phase to test the significance the effect of exogenous variables on endogenous variables. From the research results obtained, it can be concluded Service Excellent have positive and significant effect on Quality Service , Service Excellent have positive and significant effect on Patient Satisfaction, Service Quality have positive and significant effect on Quality Service, Service Quality have positive and significant effect on Patient Satisfaction.